Ménages pluriactifs et retraités : une majorité d'agriculteurs dans la vallée des Duyes (Alpes de Haute Provence) - Ponchelet D.; Bellon S. (Systèmes d'élevage et gestion de l'espace en montagnes et collines méditerranéennes, 1999)
In the Duyes valley (northern Provence) a large number of farms consist of pluriactive households or are managed by retired farmers. Other farm managers, the so-called 'neofarmers', have entered farming with no agricultural or even rural background and thus accomplished a threefold mutation: social, professional and geographic. As a result, the modes and role of farming activity display wide diversity both as regards time allocated and income. Our paper had two objectives. The first was to analyse farm diversity from a socio-economic viewpoint, paying particular attention to the non-standard farming patterns adopted. The second was to identify and analyse farmer motivations to operate in such a context. We combined two sources of information: (i) data derived from the 1988 French National Agricultural Census, which show the extent of part-time farming in a total population comprising 184 farm households; and (ii) information from 35 interviews which enabled us to assess household trajectories, motivations and regulations.